(untitled) (Journal of Naval Architecture and Marine Engineering, 2017)
Electrical Discharge Machining (EDM) process is one of the most widely used methods for machining. This method is used to form parts that conduct electricity. This method of machining has used for hard materials and therefore select the correct values of parameters are so effective on the quality machining of parts. D3 steel has a high abrasion resistance at low temperatures therefore can be a good candidate for this method of machining. Also because of high hardness and low distortion during heat treatment, using this method is economical for this alloy. The purpose of this paper is to investigate the influence of the main parameters such as voltage, current, pulse duration and pulse off time and the interaction of them to determine the optimal condition for the D3 steel alloy (alloy with DIN 1.2080). Chip removal rate (MRR) and surface quality of parts were evaluated as the output characteristic of the study. The optimum conditions were achieved when the MRR is in the highest value and surface roughness is in the lowest one. For investigation of interaction, two kinds of DOE methods (Taguchi and determinant of optimal experimental design) are used. Then the optimal parameters are investigated with the help of the analysis signal to noise (S/N) and mathematical modeling. The optimize results were tested again and compared. Also the results showed that regression modeling has better accuracy than the S/N analysis. This is because of a greater number of experiments that done in this part and taking into account the interaction parameters in the regression model.